Tuning Mechanical Properties of Polymeric Hydrogels Using Orthogonally Functionalized Crosslinkers - Bin Liu; Zhaoyan Hou; Yi Bao; Lei Hua; Xiao Wang; Yuanyuan Li; Lanying Zhou; Zhuo Lv (Advances in Polymer Technology)
A unique orthogonal crosslinker-induced hydrogel, whose mechanical strength can be tunable by the crosslinker topology upon thermal treatment, is described herein. The crosslinker containing cationic moieties and crosslinkable styrenyl groups was employed for the preparation of orthogonally crosslinked hydrogels having ionic and covalent characteristics. The manipulation of the orthogonal crosslinkers topology and the ionic bond strength between cationic and anionic moieties facilitated the control of the mechanical properties. Short-term temporal modulation of hydrogel moduli, a key factor of the substrates for cell development, was demonstrated and could provide dynamic microenvironment for biological process. In addition, on-demand control of the elastic properties of the hydrogels by application of a thermal stimulus provides new avenues to regulate cell growth. Furthermore, the orthogonality of the crosslinkers allowed molecular functionalization of a wide range of molecules of interest to the hydrogels by thiol-ene Michael addition (nucleophilic addition of sulfhydryl and carbon-carbon double bonds) in a friendly manner as demonstrated in our work.